Outsider ethnic minorities and wage determination in China. - MACDONALD, Andrew W.; HASMATH, Reza (International Labour Review, 2019)
While some studies on urban ethnic minorities in China indicate that they earn lower wages relative to the Han majority, others show little evidence of this gap. To understand this contradiction, the authors propose that the primary issue is a failure to fully disaggregate ethnic minority groups' labour market experiences. Leveraging a large data set looking at China's ethnic minorities, findings suggest that "outsider minorities", such as Tibetans and Turkic groups, suffer a significant wage penalty when controlling for covariates, while minorities in aggregate do not. These findings are robust across various specifications and have notable theoretical and policy implications.